Determinant factor Age Marry First on region urban and rural in Province Java Middle - Urip Tri Wijayanti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Based on Susenas 2017 data, 17.52 percent of women in Central Java Province were married under the age of 20. years later SKAP 2019 there were 36.4 percent. The purpose of this study was to determine the determinants of the age of first marriage in urban and rural areas in Central Java province. Quantitative research type by using data SKAP Central Java secondary data 2019. Sampling was carried out using systematic random sampling for households selected, then women of childbearing age aged 15-49 years were taken. The unit of analysis was all women of childbearing age with the status married for the first time under 20 years old. Based on the results of the data selection, 971 people were obtained women. Research design The cross-sectional method used is cross-sectional. The results are factors related to the age of first marriage. under 20 years in urban and rural areas are factors of education and welfare level. Factors occupation, age of first sexual intercourse and media exposure to KRR information are not related to the age of first marriage under 20 years in urban and rural areas. Recommendations for Representative National Population and Family Planning Agency Province Java Middle the more intense do Communication Information And Education (IEC) about maturity age marriage especially on region rural.